2018
DOI: 10.1016/j.aninu.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of on-range choice feeding with black soldier fly larvae (Hermetia illucens) on flock performance, egg quality, and range use of free-range laying hens

Abstract: Semi-intensive free-range farm systems are common in Australia, and these systems frequently practise on-range feeding. The objective of this study was to investigate the benefit of on-range choice feeding on flock performance, egg quality, and range use of free-range laying hens using black soldier fly larvae (Hermetia illucens, BSF). A total of 160 mature ISA brown laying hens, previously determined to range daily, were allocated to a control group (control) or a treatment group (BSF) with various replicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…Our hypothesis is that the significantly (p = 0.032) augmented length of the jejunum found in the HI25 and HI50 hens, being respectively 4.68 and 4.64 (as percentage of the live weight), compared to the C one (3.45% live weight), [14] could have promoted the absorption of the amino acids, hence resulting in a higher assumption of these nutrients. This possible explanation strongly needs the support of other comprehensive studies, since the effect of HI meal on hen egg weight is still scarcely investigated and conflicting in results [13,24]. The increased egg weight found with the HI meal inclusion in the hens' diet may require an increase in eggshell weight because of a rising in calcium deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis is that the significantly (p = 0.032) augmented length of the jejunum found in the HI25 and HI50 hens, being respectively 4.68 and 4.64 (as percentage of the live weight), compared to the C one (3.45% live weight), [14] could have promoted the absorption of the amino acids, hence resulting in a higher assumption of these nutrients. This possible explanation strongly needs the support of other comprehensive studies, since the effect of HI meal on hen egg weight is still scarcely investigated and conflicting in results [13,24]. The increased egg weight found with the HI meal inclusion in the hens' diet may require an increase in eggshell weight because of a rising in calcium deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Although the egg production and quality as affected by H. illucens in laying hen diets have been recently examined [11][12][13]24], the focus areas were the egg deposition and quality characteristics as the albumen height, the yolk color and its chemical composition. Nonetheless, the albumen has relevant importance for the egg industry mainly because of its unique functional properties, such as foaming that promote its extensive use as an ingredient in several processed food.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were obtained by Secci et al [97], who recently tested the effects of the total replacement of SBM with HI larva meal in laying hen diets (Lohmann Brown Classic) and they have reported a higher proportion of yolk in the eggs, as well as higher amounts of γ-tocopherol, lutein, β-carotene and total carotenoids in HI-fed birds. Ruhnke et al [98] instead showed a decrease in egg weight, shell weight and thickness, as well as a decrease in the intensity of the yolk color in free-range laying hens fed HI larva meal.…”
Section: Product Qualitymentioning
confidence: 99%
“…The use of defatted BSF larvae meal as feed for laying hens has been previously reported [2,3,4,9]. Indeed, feeding defatted BSF meal to laying hens was shown to either increase [10,11] or decrease [12,13] eggshell thickness and eggshell strength. Moreover, BSF larvae meal has been found to contain chitin [14,15], an indigestible substance.…”
Section: Introductionmentioning
confidence: 99%